Updated list of Collembola species currently recorded from South Africa - (:unkn) unknown (My University, 2015)
Understanding the abundance and richness of species is one of the most fundamental steps in effecting their conservation. Despite global recognition of the significance of the below-ground component of diversity for ecosystem functioning, the soil remains a poorly studied terrestrial ecosystem. In South Africa, knowledge is increasing for a variety of soil faunal groups, but many still remain poorly understood. We have started to address this gap in the knowledge of South African soil biodiversity by focusing on the Collembola in an integrated project that encompasses systematics, barcoding and ecological assessments. Here we provide an updated list of the Collembola species from South Africa. A total of 124 species from 61 genera and 17 families has been recorded, of which 75 are considered endemic, 24 widespread, and 25 introduced. This total number of species excludes the 36 species we consider to be dubious. From the published data, Collembola species richness is high compared to other African countries, but low compared to European countries. This is largely a consequence of poor sampling in the African region, as our discovery of many new species in South Africa demonstrates. Our analyses also show that much ongoing work will be required before a reasonably comprehensive and spatially explicit picture of South Africa's springtail fauna can be provided, which may well exceed 1000 species. Such work will be necessary to help South Africa meet its commitments to biodiversity conservation, especially in the context of the 2020 Aichi targets of the Convention on Biological Diversity.
Keywords: African Research